Problematyka etyki politycznej w badaniach politologicznych - Ossowski, Szymon (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2008)
The opinions presented in the paper and the problems raised in the considerations on political ethics confirm that there is no holistic, systematic approach to political ethics as a significant realm of research, or even a separate subdiscipline within political science. Although the issues discussed in the paper are significant and interesting, they do not create a cohesive and holistic research proposal. These are significant opinions in the discussion on the problem of political ethics, yet they are limited to the analysis of detailed issues. Therefore, it is necessary to identify an appropriate method to study political ethics from the point of view of political science.